Rewrite 1/2 to have a common denominator with 2/6
1/2 x 3 = 3/6
Now you have 1 and 3/6 - 2/6 = 1 and 1/6
Now rewrite 2/3 to have a common denominator with 1/6: 2/3 x 2 = 4/6
Subtract 1/6 from 4/6:
4/6 - 1/6 = 3/6 = 1/2
You will need to add 1/2
To get from the difference between 1 and 1/2 and 2/6 to 1 and 2/3, one must add 1/2 after ensuring both differences have a common denominator.
To find out what should be added to the difference between 1 and 1/2 and 2/6 to get 1 and 2/3, we need to perform a few steps involving fractions. First, let's convert 1 and 1/2 into an improper fraction by multiplying 1 (the whole number) by 2 (the denominator of the fractional part) and adding 1 (the numerator of the fractional part), which gives us 3/2. Now, to find the difference between 3/2 and 2/6, we must have a common denominator, which is 6 in this case. Multiplying the numerator and denominator of 3/2 by 3 gives us 9/6.
Now we subtract 2/6 from 9/6 to get the difference, which is 7/6 or 1 and 1/6. To find what needs to be added to this difference to get 1 and 2/3, we must also express 1 and 2/3 as an improper fraction. Multiplying 1 (the whole number) by 3 (the denominator) and adding 2 (the numerator) gives us 5/3.
To compare 7/6 with 5/3, we need the same denominator, which is 6. So we multiply the numerator and denominator of 5/3 by 2 to get 10/6. Subtracting 7/6 from 10/6, we find the missing number to be 3/6, which simplifies to 1/2.
Translate "the sum of 6 and the product of 8 and x” into a mathematical expression
The mathematical expression is 6 + 8x
The sum of 6 and the product of 8 and x can be written mathematically by first getting the product of 8 and x which equals 8x
Sum means addition( +)
So the sum of 6 is written as 6 +
We thus have the mathematical expression Translated as 6 + 8x
See related answer using this link: https://brainly.com/question/12593943
The mathematical expression for 'the sum of 6 and the product of 8 and x' is 6 + 8x.
Explanation:A mathematical expression is a combination of numbers, variables, and mathematical operators (e.g., +, -, *, /) that represents a calculation or relationship. Expressions can be simple, like 2x + 3, or complex, serving various purposes in mathematical modeling, calculations, and problem-solving.
To translate the phrase 'the sum of 6 and the product of 8 and x' into a mathematical expression, we can use the symbols and operations of algebra. The sum of 6 and the product of 8 and x can be written as 6 + 8x. Here, 8x represents the product of 8 and x, and the addition symbol, '+', represents the sum of 6 and 8x.
Learn more about Translating phrases into mathematical expressions here:https://brainly.com/question/29174775
#SPJ11
Ali, Ben and Joe sell 73 raffle tickets between them. Ben sells twice as many tickets as Ali, and Joe sells 8 more tickets than Ben. How many tickets does each person sell?
Answer:
Ali-13
Ben-26
Joe-34
Step-by-step explanation:
Ali-x
Ben-2x
Joe-2x+8
x+2x+2x+8=73
3x+2x+8=73
5x+8=73
5x=73-8
5x=65
x=65/5
=13
Ali sells 13 tickets
Ben sells 13×2
=26 tickets
Joe sells (13×2)+8
=34 tickets
Ali sells 13 tickets. Ben sells 26 tickets. Joe sells 34ctickets
How many tickets does each person sell?Let
Ali = x
Ben = 2x
Joe = 2x+8
⇒ x+2x+2x+8=73
⇒ 3x+2x+8=73
⇒ 5x+8=73
⇒ 5x=73-8
⇒ x=65/5
⇒ 13
Ali sells 13 tickets.
Ben sells 13×2
= 26 tickets.
Joe sells (13×2)+8
= 34 tickets.
An equation is a mathematical statement that is made up of two expressions connected by an equal sign.
Learn more about the equation here: https://brainly.com/question/1214333
#SPJ2
What is the measure of angle COA?
140°
150°
160°
170°
Answer:160
Step-by-step explanation:
To solve the problem we must know the concept of the Center angle theorem. The measure of the center angle ∠AOC is 160°.
What is the central angle theorem?According to the central angle theorem, if an arc of a circle makes an angle with any point on the circumference of that circle then the measure of that angle is half the angle made by that arc at the center of the circle.
Given to us
∠ABC = 80°
As we already know the angle made by Arc AC at point B, therefore, the center angle made by ARC AC at the center will be twice of it. Therefore,
∠AOC = 2∠ABC
∠AOC = 2(80°)
∠AOC = 160°
Hence, the measure of the center angle ∠AOC is 160°.
Learn more about Center Angle:
https://brainly.com/question/25889947
A hot air balloon is at a height of 2250 feet.It descends 150 feet each minute.Find its height after 6,8,and 10 minutes.
.Make a table to show the pattern of heights.
.Write an expression for the balloon height at m minutes.
Answer:
equation: y=-150m+2250
Height after:
6 Minutes: 1350 ft
8 Minutes: 1050 ft
10 Minutes: 750 ft
Step-by-step explanation:
We know that the hot air balloon has an initial height of 2250 ft, so that is our y-intercept (in the equation, y =mx+b, the y-intercept is b). Next you know that after every minute, the balloon goes down 150 ft. So that means -150 ft per minute. Now put it together, the equation is written as "y = 150m+2250" (since m is the required variable, that's what is written in the equation instead of x).
Next, to make a table, you need to determine what value goes in the left side, the x values (the independent variables) and what goes in the right side, the y values (the dependent variables). The two variables here are Height and Time. Time is not dependent on the height of the balloon-- the height depends on how much time has passed. So Time on the left and height on the right. Next just plug in the values 6, 8, and 10 into your equation. Your answer will be the output, aka the height of the hot air balloon after x minutes.
Your table should look something like this:
m y
6 1350
8 1050
10 750
Hope this helps :)
A number cube with the numbers 1 through 6 is rolled. What is the theoretical probability, as a decimal, of the number cube showing a 1? Round the decimal to the nearest hundredth.
Answer:
0.17
Step-by-step explanation:
The numbers are from 1 to 6 on each side.
The total sample space will be 6.
Denoted as:
n(S) = 6
There will be only one outcome as 1
So,
Let A be the event that the number is 1
Then,
n(A) = 1
[tex]P(A) = \frac{n(A)}{n(S)} \\=\frac{1}{6} =0.166[/tex]
Hence the theoretical probability of the number cube showing a 1 is 0.166 ..
Rounding off to the nearest hundred
0.17 ..
Find all solutions to the equation. (1 point) sin x = square root of three divided by two.
Answer:
x=pi/3 + 2pi*k
x=2pi/3+2pi*k
Step-by-step explanation:
sin(x)=sqrt(3)/2
This happens twice in the first rotation on our unit circle.
It happens in the first quadrant and in the second quadrant. Third and fourth quadrants are negative for sine.
So we are looking for when the y-coordinate on the unit circle is sqrt(3)/2.
This is at pi/3 and 2pi/3.
So we can get all the solutions by adding +2pi*k to both of those. This gives us a full rotation about the circle any number of k times. k is an integer.
So the solutions are
x=pi/3 + 2pi*k
x=2pi/3+2pi*k
An equation is formed of two equal expressions. The solution to the equation sin(x)=√3/2 is (π/3 ± 2πn), (2π/3 ± 2πn), where n is any natural number.
What is an equation?An equation is formed when two equal expressions are equated together with the help of an equal sign '='.
The solution of sinx=√3/2 are,
sin(x) = √3/2
x = sin⁻¹ √3/2
x = (π/3 ± 2πn), (2π/3 ± 2πn)
Hence, the solution to the equation sin(x)=√3/2 is (π/3 ± 2πn), (2π/3 ± 2πn), where n is any natural number.
Learn more about Equation:
https://brainly.com/question/2263981
#SPJ2
Lisa's barn has 20 animals that have 62 legs in total. She only has cows and geese. How many cows and how many geese does she have?
Answer:
9 geese
11 cows
Step-by-step explanation:
Say x is cows, and y is geese.
x + y = 20 animals
x * 4 + y * 2 = 62
x = 20 - y
(20 - y) * 4 + y * 2 = 62
80 - 4y + 2y = 62
- 2y = -18
y = 9 geese
x = 20 - 9 = 11 cows
Lisa has 11 cows and 9 geese.
To solve the problem involving Lisa's barn with 20 animals having 62 legs in total, and knowing she only has cows and geese, we can use a system of linear equations. We can denote the number of cows as c and the number of geese as g. Cows have 4 legs and geese have 2 legs.
We can then set up the following equations based on the information given:
Cows and geese equation: c + g = 20 (since there are 20 animals in total)
Legs equation: 4c + 2g = 62 (because cows have 4 legs and geese have 2 legs)
Now, let's solve the system of equations:
Multiply the first equation by 2 to match the number of geese legs in the second equation: 2c + 2g = 40
Subtract the modified first equation from the legs equation: (4c + 2g) - (2c + 2g) = 62 - 40, which simplifies to 2c = 22, and then c = 11. Lisa has 11 cows.
Substitute the number of cows back into the first equation to find the number of geese: 11 + g = 20, which leads to g = 9. Lisa has 9 geese.
Therefore, Lisa has 11 cows and 9 geese.
Write the Recursive rule for the geometric sequence
An=1072-1
8, 4, 2, 1, 1/2,...
[tex]\bf 8~~,~~\stackrel{8\cdot \frac{1}{2}}{4}~~,~~\stackrel{4\cdot \frac{1}{2}}{2}~~,~~\stackrel{2\cdot \frac{1}{2}}{1}~~,~~\stackrel{1\cdot \frac{1}{2}}{\cfrac{1}{2}} \\\\\\ a_n=\cfrac{1}{2}\cdot a_{n-1}\qquad \begin{cases} a_1=\textit{previous term}\\ a_n=\textit{current term}\\ a_1=\textit{first term}\\ \qquad 8 \end{cases}[/tex]
Which system of equations has only one solution?
Answer:
The answer is the last option, D.
Step-by-step explanation:
A function with one solution can be added and have a variable and a constant leftover. The variables in the other three options cancel each other out, so none of them have one solution. The first and third equations have no solutions, and the second has infinitely many solutions. The fourth option has only one variable cancel out and still has a constant on the other side of the equation. The fourth option is correct.
Find the average rate of change for the given function from x = 1 to x = 2.
1) -2
2) -1/2
3) 1/2
4) 2
Answer:
2
Step-by-step explanation:
The average rate of change from x=1 to x=2 is the same as finding the slope of a line at x=1 and x=2.
So we are going to need to corresponding y coordinates.
What y corresponds to x=1? y=3
What y corresponds to x=2? y=5
So we have the ordered pairs (1,3) and (2,5).
Line the points up vertically and subtract vertically then put 2nd difference over 1st difference.
(2 , 5)
-(1 , 3)
-----------
1 2
The average rate of change is 2/1 or just 2.
Now since we were asked to find the average rate of change given the function was a line, it really didn't matter what two points you used on that line.
Answer: Fourth option
[tex]m=2[/tex]
Step-by-step explanation:
If we call m the average change rate of a function between [tex]x_1[/tex] and [tex]x_2[/tex], then, by definition:
[tex]m=\frac{f(x_2)-f(x_1)}{x_2-x_1}[/tex]
In this case the function is the line shown in the graph. Then we look for the values of [tex]y = f (x)[/tex] for [tex]x = 1[/tex] and [tex]x = 2[/tex]
When [tex]x=1[/tex] then [tex]f(x)=3[/tex]
When [tex]x=2[/tex] then [tex]f(x)=5[/tex]
Therefore
[tex]m=\frac{5-3}{2-1}[/tex]
[tex]m=\frac{2}{1}[/tex]
[tex]m=2[/tex]
The Reed High School basketball program earned $7,115.03 in profits over the current season. Based on game attendance, it is determined that the girls' basketball team will receive 7% of the profits, while the boys' basketball team will receive 11% of the profits. Which is the best estimate of how much more the boys' team will receive in profits than the girls' team?
A.
$770
B.
$490
C.
$280
D.
$1,260
Answer:
c. $280
Step-by-step explanation:
first you times the total profits by the percent that the girls get then the percent the boys get to find out how much of the profit the girls and boys basketball teams each get, then you subtract the profits the boys get by the profits the girls get to find out how much more the boys get than the girls.
7,115.03 x .07 = 498.0521
7,115.03 x .11 = 782.6533
782.6533 - 498.0521 = 284.6012
the boys receive 284.6012 more in profits than the girls
so c. $280 would be the best estimate of how much more the boys team will receive
Which statement is true regarding the graphed functions?
Answer:
Option A) f(2)=0 and g(-2)=0
Step-by-step explanation:
we know that
The vertex of f(x) is equal to (2,0)
The vertex of g(x) is equal to (-2,0)
step 1
Find the value of f(x) and g(x) for x=2
Observing the graph
For x=2
f(2)=0 ----> the y-coordinate of the vertex
g(2) > 12
step 2
Find the value of f(x) and g(x) for x=-2
Observing the graph
For x=-2
f(-2)> 12
g(-2)=0 ----> the y-coordinate of the vertex
therefore
The statement that is true regarding the graphed functions is
f(2)=0 and g(-2)=0
A graph of quadratic function y = f(x) is shown below.
What is the solution set of the quadratic inequality f(x) ≥ 0?
Answer: it’s B 0
Step-by-step explanation:
what's the answer to this?
(x+1)²=25
[tex](x+1)^2=25\\x+1=5 \vee x+1=-5\\x=4 \vee x=-6[/tex]
PLEASE URGENT
Carrie is finding the set of even numbers within the set of prime numbers.
Of the sets described, which is the universal set?
all real numbers
all integers
prime numbers
even numbers
Answer:
Prime Numbers
Step-by-step explanation:
Two sets are being considered in the given statement:
Set of even numbersSet of prime numbersA universal set is defined as such a set from which all the other subsets are taken for a given case. Or in other words, a universal set is such a set to which all the subsets belong and this universal set contains all the elements being studied/considered.
For the given case, set of Even Numbers is the subset which is being taken from the set of prime numbers. The set of prime numbers contains all the elements which we are considering for this very scenario.
Therefore, the set of prime numbers is the universal set.
Answer:
c
Step-by-step explanation:
In circle C, r = 32 units.
What is the area of circle C?
Answer:
A = 1024π units², A ≈ 3216.99 units²
Step-by-step explanation:
The equation of the area of a circle is A = πr², where A = area and r = radius.
Given that, we can plug in r as 32 units: A = π(32 un.)²
Simplifying that gives us A = 1024π units², or A ≈ 3216.99 units²
Which expression is equivalent to (2mn)^4/6m^-3n^-2? assume m and n cannot equal 0
Answer:
=8/3m⁷n⁶
Step-by-step explanation:
Given the expression (2mn)⁴/6m⁻³n⁻², we first solve the numerator
(2mn)⁴ = 16m⁴n⁴
The new expression becomes 16m⁴n⁴/6m⁻³n⁻²
We now divide the coefficients and the exponents as follows:
=16/6ₓ(m⁴/m⁻³)×(n⁴/n⁻²)
Division between indices to the same base we subtract the powers.
4-⁻3=7
4-⁻2=6
=8/3m⁷n⁶
Answer:
the asnwer is A
Step-by-step explanation:
Evaluate P(5, 3). 15 20 60
Answer:
20.
Step-by-step explanation:
P(5,3) = 5! / 3!
= (5*4*3*2*1) / (3*2*1)
= 20.
If sin theta =7/25, use the Pythagorean identity to find cos theta
Answer:
[tex]\cos(\theta)=\pm \frac{24}{25}[/tex]
Step-by-step explanation:
I don't know where [tex]\theta[/tex] is so there is going to be two possibilities for cosine value, one being positive while the other is negative.
A Pythagorean Identity is [tex]\cos^2(\theta)+\sin^2(\theta)=1[/tex].
We are given [tex]\sin(\theta)=\frac{7}{25}[/tex].
So we are going to input [tex]\frac{7}{25}[/tex] for the [tex]sin(\theta)[/tex]:
[tex]\cos^2(\theta)+(\frac{7}{25})^2=1[/tex]
[tex]\cos^2(\theta)+\frac{49}{625}=1[/tex]
Subtract 49/625 on both sides:
[tex]\cos^2(\theta)=1-\frac{49}{625}[/tex]
Find a common denominator:
[tex]\cos^2(\theta)=\frac{625-49}{625}[/tex]
[tex]\cos^2(\theta)=\frac{576}{625}[/tex]
Square root both sides:
[tex]\cos(\theta)=\pm \sqrt{\frac{576}{625}}[/tex]
[tex]\cos(\theta)=\pm \frac{\sqrt{576}}{\sqrt{625}}[/tex]
[tex]\cos(\theta)=\pm \frac{24}{25}[/tex]
diameter of a circular garden pool is six feet. what is the area of the pool in algebra
For this case we have that by definition, the area of a circle is given by:
[tex]A = \pi * r ^ 2[/tex]
Where:
r: It is the radius of the circle
As data we have that[tex]r = 6 \ ft[/tex]
Then, replacing we have:
[tex]A = \pi * 6 ^ 2\\A = 36 \pi[/tex]
Taking [tex]\pi = 3.14[/tex]
A = 113.04
So, the pool area is [tex]113.04 \ ft ^ 2[/tex]
Answer:
[tex]113.04 \ ft ^ 2[/tex]
Answer:
9π ft²
Step-by-step explanation:
Given that (-3,7) is on the graph of f(x), find the
corresponding point for the function f- 3/4x
Answer:(4, 7)
Step-by-step explanation:
This question is about changing the coordinates of the function.
They want you to choose a value of x that will make the sentence inside the function (-3x/4) equal to -3.
-3 x / 4 = -3
x = 4
Hence, the correspondig point is (4, 7)
Jack and Jillian sell apples at a produce stand. Jillian earns $2 for each bag of apples she sells. At the end of the week, Jack has earned $8 less than Jillian. The following expression shows Jack's earnings: 2x − 8 In the expression, what does the first term represent? Jack's earnings at the end of the week The number of bags of apples Jillian sold Jillian's earnings at the end of the week The number of bags of apples Jack sold
Answer:
The first term (2x) represents Jillian's earnings at the end of the week. Where the 2 represents the amount of money she earns per pag, and the 'x' is the number of bags sold.
Let us explain this with an example: if Jillian sells 36 bags, then she will earn 2×36 = $72
Answer:
option C is true.
Step-by-step explanation:
We are given that Jack and Jillian sell apples at a produce stand .
We are given that an expression which shows Jack's earning=2x-8
We have to find that first term what represent in the given expression
Jillian earns for each bag of apples she sells=$2
Let Jillian sold number of bags of apples =x
Then ,Jillian earn total at the end of the week =[tex]2\timesx=$2x[/tex]
Jack has earned $ 8 less than Jillian earn
Therefore, total earning of jack=[tex]2x-8[/tex]
In the given expression the first term 2x represent the earning of Jillian.
Hence, option C is true.
Answer: C: JIllian's earning at the end of the week
Anja divides (8x3 - 36x2 + 54x - 27) by (2x - 3) as shown below. What error does Anja make?
4x2 - 12x+9
2x-3) 8x2 – 36x2 + 54x-27
8x3–1282
-24x2 + 54 x
-24x2 + 36%
18x-27
18x+27
-54
She makes a subtraction error
She makes an error choosing the x-term in the quotient.
She makes a multiplication error
She makes an error rewriting the problem in long division
Answer:
There is a multiplication error
Step-by-step explanation:
Long division method is used to divide greater number by a smaller number.
Here, greater number is known as the dividend and smaller number is known as divisor.
As per division algorithm,
Dividend = Divisor [tex]\times[/tex] quotient + remainder
Here, dividend = [tex]8x^3-36x^2+54x-27[/tex]
Divisor = [tex]2x-3[/tex]
Here, we need to find the error in the long division .
In step:
[tex]18x+27[/tex] , it should be 18x-27 as [tex]-3\times 9=-27[/tex] not +27
So, there is a multiplication error .
The correct option is c) she makes a multiplication error.
Step-by-step explanation:
Given :
Dividend = [tex]8x^3-36x^2+54x-27[/tex]
Divisor = [tex]2x-3[/tex]
Solution :
In step [tex]18x +27[/tex] there is mistake. It should be [tex]18x - 27[/tex] because [tex]-3 \times 9= -27[/tex] not +27.
Therefore the correct option is c) she makes a multiplication error.
For more information, refer the below link
https://brainly.com/question/21416852?referrer=searchResults
Solve for variable: 5z/8 – 1/3 = 2/5
Answer: z= .6
Step-by-step explanation:
Numerator: When you do 5•.6, you get 3, and then 3-1 equals 2.
Denominator: 8 - 3 = 5.
Therefore you get 2/5 which makes z = .6
Amir stands on a balcony and throws a ball to his dog, who is at ground level.
The ball's height (in meters above the ground), xxx seconds after Amir threw it, is modeled by
h(x)=-(x+1)(x-7)
How many seconds after being thrown will the ball reach its maximum height?
________ seconds
I know I literally just posted one a couple minutes ago but, please help me again T-T
Answer:
3 seconds
Step-by-step explanation:
The given equation describes a parabolic curve with zeros at x=-1 and x=7. The line of symmetry of the curve is halfway between the zeros, at ...
x = (-1 +7)/2 = 6/2 = 3
The maximum of the curve is on the line of symmetry. The ball will reach its maximum height 3 seconds after being thrown.
_____
Additional comment
The maximum height will be 16 meters.
The ball will reach its maximum height 3 seconds after being thrown.
Explanation:To find the time when the ball reaches its maximum height, we need to determine the vertex of the quadratic equation representing the ball's height. The equation h(x)=-(x+1)(x-7) can be rewritten in vertex form as h(x)=-x^2+6x-7. The x-coordinate of the vertex can be found using the formula x = -b/2a, where a, b, and c are the coefficients of the quadratic equation.
In this case, a = -1 and b = 6. Plugging these values into the formula, we get x = -6/-2 = 3. Therefore, the ball reaches its maximum height 3 seconds after being thrown.
SEE IMAGE! Two lines below intersect to form four angles, as shown. The measure of angle 2 is 114°. What is the sum of the measures of angles 1 and 3?
A) 66
B) 90
C) 114
D) 132
Will mark brainliest, please answer :)
The question is in the picture above
Answer:
6√10 ≈ 19.0
Step-by-step explanation:
The length of the diagonal is:
d² = w² + l² + h²
Given d = 36, l = 30, and h = 6:
36² = w² + 30² + 6²
1296 = w² + 900 + 36
w² = 360
w = 6√10
w ≈ 19.0
The box should be approximately 19 inches wide.
An animal shelter estimates that it costs about $6 per day to care for each dog. If y represents the total cost of caring for a single dog for x days, which table models the situation?
Answer:
x y
6 36
9 54
12 72
Step-by-step explanation:
The options are shown in the pictures attached.
Data:
a single dog costs about $6 per day
y-variable represents the total cost
x-variable represents days
So, 1 day costs $6, 2 days costs 2*$6 = $12, 3 days costs 3*$6 = $18 and so on. Then, the table is:
x y
6 6*6 = 36
9 9*6 = 54
12 12*6 = 72
What is the value of 4a^3–2b^2+5 when a = 3 and b =–2
Answer:
105
Step-by-step explanation:
Evaluate 4 a^3 - 2 b^2 + 5 where a = 3 and b = -2:
4 a^3 - 2 b^2 + 5 = 4×3^3 - 2×(-2)^2 + 5
3^3 = 3×3^2:
4×3×3^2 - 2×(-2)^2 + 5
3^2 = 9:
4×3×9 - 2×(-2)^2 + 5
3×9 = 27:
4×27 - 2×(-2)^2 + 5
(-2)^2 = 4:
4×27 - 24 + 5
4×27 = 108:
108 - 2×4 + 5
-2×4 = -8:
108 + -8 + 5
| | 1 |
| 1 | 0 | 8
+ | | | 5
| 1 | 1 | 3:
113 - 8
| | 0 | 13
| 1 | 1 | 3
- | | | 8
| 1 | 0 | 5:
Answer: 105
Answer:
105
Step-by-step explanation:
4a^3 -2b^2 +5
Let a=3 and b= -2
4 (3)^3 -2 (-2)^2 +5
4 *27 -2 (4) +5
108 -8+5
105
Write an equation: The sides of a rectangle are x and ( x - 4 ). The perimeter is 87
The perimeter of a rectangle, is all of the sides added up.
In a rectangle, there are two widths (right and left), and two lengths (up and down)
So:
Perimeter = 2 × width + 2 × length.
To get the equation we just substitute in the values that we are given:
length = (x)
width = (x - 4)
perimeter = 87
So just put these values into: perimeter = 2 × width + 2 × length:
87 = 2(x) + 2(x - 4)
_____________________________
Answer:
The equation is: 87 = 2(x) + 2(x - 4)
(note: this can be simplified down like so:
87 = 2x + 2x - 8
87 = 4x - 8
95 = 4x
23.75 = x
)